Prevalence, risk factors, and prognosis of interstitial lung disease in a large cohort of Chinese primary Sjögren syndrome patients: A case-control study. Issue 24 (June 2018) - Gao, Hui; Zhang, Xue-Wu; He, Jing; Zhang, Jing; An, Yuan; Sun, Ye; Jia, Ru-Lin; Li, Sheng-guang; Zhang, Li-jing; Li, Zhan-Guo
Abstract : Abstract: To determine the prevalence of pulmonary complications in primary Sjögren syndrome (pSS), and to identify the risk factors and the prognosis associated with pulmonary involvement in pSS patients. A total of 1341 hospitalized patients (853 with pSS and 488 with secondary Sjögren syndrome [sSS]) were retrospectively reviewed. Of these, 165 hospitalized patients with pSS-associated interstitial lung disease (ILD) were analyzed and recruited as a study group. Eighty-four pSS patients without organ damage were included as a control group. One hundred and sixty-five patients (19.34%) from the pSS group and 126 patients (25.82%) from the sSS group presented with lung involvement. Of the 165 pSS patients with lung complications, 151 (91.5%) were women. The mean age was 61.25 ± 9.79 years, and the median disease duration was 84 (24–156) months. Non-specific interstitial pneumonia (NSIP; 39.1%) was the predominant pattern on high-resolution computed tomography (HRCT). The total HRCT score was 9.71 ± 4.77. Impairment in diffusion capacity was the most common (74.3%) and severe complication (predicted value of T LCO was 57.5 ± 21.2%). The 5-year survival rate for all patients with pSS-ILD was 88.5%. Age, disease duration, rheumatoid factor (RF), and C-reactive protein (CRP) were significantly higher than in controls, whereas anti-SSA was less common. Age, RF, and CRP were independent predictors of ILD after adjustment for confounders. Lung involvement is a common and severe complication of Sjögren syndrome. Age and disease activity are correlated with pulmonary involvement in pSS patients. Abstract : Supplemental Digital Content is available in the text